Effects of Immunosuppressive Drugs on Viability and Susceptibility of Adipose- and Bone Marrow-Derived Mesenchymal Stem Cells - Tsuji, Wakako; Schnider, Jonas T.; McLaughlin, Meghan M.; Schweizer, Riccardo; Zhang, Wensheng; Solari, Mario G.; Rubin, J. Peter; Marra, Kacey G.; Plock, Jan A.; Gorantla, Vijay S. (Frontiers in Immunology, 2015)
The immunomodulatory potential of cell therapies using adipose-derived stem cells (ASCs) and bone marrow-derived mesenchymal stem cells (BM-MSCs) has been studied in vascularized composite allotransplantation (VCA). Most cell therapy-based experimental and clinical protocols integrate some degree of recipient conditioning/induction with antibodies or other immunosuppressive agents on the functional and morphological properties of stem cell, and consequent efficacy of therapy outcomes. We investigate the susceptibility of ASCs and BM-MSCs to anti-lymphocyte serum (ALS) and tacrolimus. Rat ASCs and BM-MSCs were exposed to varying concentrations of tacrolimus and ALS in vitro. Serum from ALS-treated animals was added to cell cultures. Viability, susceptibility, and cytotoxicity parameters were evaluated. ALS inhibited ASC and BM-MSC viability and susceptibility in vitro in a dose dependent manner. ASCs were more susceptible to both ALS and tacrolimus than BM-MSCs. Trypsinized and adherent ASCs were significantly smaller than BM-MSCs. This is the first report on the viability and susceptiblity characteristics of BM-MSCs or ASCs to collateral effects of ALS and tacrolimus. These in vitro insights are important regarding choice of cell type as well as concomitant conditioning agents and the logistical coordination of the timing, dosing and frequency of drug or cell therapy in SOT or VCA protocols.